Research on Insurance Industry Based on AR3 Multi Risk Model - Cao, Junjia; Liu, Zhuodong; Lei, Xi (Transactions on Economics, Business and Management Research, 2024)
The increasing frequency of extreme weather events presents challenges for the insurance industry, necessitating the construction of models for its development and offer insights and inspiration for real estate and community. In the current climate, aiming to enhance decision-making for insurance companies, this paper firstly establishes the AR3 Multi-Hazard Insurance Model incorporates three primary indicators of resilience, recovery, and adaptability, as well as secondary and tertiary indicators such as Insurance Penetration Rate (IPR), to evaluate regional disaster coping capabilities, whose weights are calculated using the E-AHP model. Additionally, the Climate Risk Insurance Model (CRIM) is established which utilizes the ARIMA model for data forecasting over the next 10 years and calculates the relationship between insurance costs and claims to indicate that it’s unfeasible for insurance policies to be held in the California from 2029 to 2033 and in Queensland for 2028, and from 2031 to 2033. The results of the models are also used to determine the insurance company’s risk strategies and how individuals can influence such strategies.